If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3b + -2) + 11 = 106 Reorder the terms: 5(-2 + 3b) + 11 = 106 (-2 * 5 + 3b * 5) + 11 = 106 (-10 + 15b) + 11 = 106 Reorder the terms: -10 + 11 + 15b = 106 Combine like terms: -10 + 11 = 1 1 + 15b = 106 Solving 1 + 15b = 106 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 15b = 106 + -1 Combine like terms: 1 + -1 = 0 0 + 15b = 106 + -1 15b = 106 + -1 Combine like terms: 106 + -1 = 105 15b = 105 Divide each side by '15'. b = 7 Simplifying b = 7
| 6(1+7x)+7(3x-1)=-64 | | -8x-4=-20 | | .8x+22.5=.7x+63 | | -4+6x=-40 | | (2ab^2c^2)(4a^3b^2c^2)= | | x=(5y+4)/(4y+3) | | 25n^3/15n^3 | | 9+2/3x=1+1x | | -7(t+2)=28 | | 10x^2-7x+2=0 | | -2.7z(z+1.5)=1.8(z+4) | | 4(t-1)=17-t | | -17=4(-5x-3)+5(2x-1) | | 21+9/3+9 | | 5x=195.5 | | 34-19=5(x-6) | | y=125x | | 51=-6(1+2a)-5(-1+8a) | | 5t=12 | | 5(x-3)+4= | | 2x+7+3x=x+27 | | (x-7/4)=1-(x/7) | | -1/9(63+4) | | 4-6x=4x+6 | | 5+2x=5x-13 | | 5w+12=3w-8 | | 12x-20=7x+45 | | -1/9(62+4) | | 4(x-4)-r+2x=5(3x-7)-9x | | 4(b+2)=3(b-7) | | 1.3(8-6)+3.7b=-5.2 | | 2+(y/3)=(4y/9)-4 |